2003
DOI: 10.1046/j.1460-9568.2003.02544.x
|View full text |Cite
|
Sign up to set email alerts
|

α2‐Adrenoreceptor activation inhibits LTP and LTD in the basolateral amygdala: involvement of Gi/o‐protein‐mediated modulation of Ca2+‐channels and inwardly rectifying K+‐channels in LTD

Abstract: Activation of adrenoreceptors modulates synaptic transmission in the basolateral amygdala. Here, we investigated the effects of alpha2-adrenoreceptor activation on long-term depression and long-term potentiation in an in vitro slice preparation of the mouse basolateral amygdala. Field potentials and excitatory postsynaptic currents were evoked in the basolateral amygdala by stimulating the lateral amygdala. Norepinephrine (20 micro m) reduced synaptic transmission and completely blocked the induction of long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 56 publications
(74 reference statements)
9
57
1
Order By: Relevance
“…2 C and F; n ϭ 6, t test, P ϭ 0.28). This observation is surprising because it has been demonstrated previously that NE, acting on specific adrenoreceptor subtypes, could either inhibit or facilitate glutamatergic synaptic transmission in lateral or basal nuclei of the amygdala (17)(18)(19)(20). In agreement with previous studies, we found that activation of ␤-adrenoreceptors by 10 M NE in the presence of the ␣ 2 -adrenoreceptor antagonist yohimbine (20 M) led to potentiation of the thalamo-amygdala EPSC to 149 Ϯ 10% of its initial value ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…2 C and F; n ϭ 6, t test, P ϭ 0.28). This observation is surprising because it has been demonstrated previously that NE, acting on specific adrenoreceptor subtypes, could either inhibit or facilitate glutamatergic synaptic transmission in lateral or basal nuclei of the amygdala (17)(18)(19)(20). In agreement with previous studies, we found that activation of ␤-adrenoreceptors by 10 M NE in the presence of the ␣ 2 -adrenoreceptor antagonist yohimbine (20 M) led to potentiation of the thalamo-amygdala EPSC to 149 Ϯ 10% of its initial value ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…There are two reports from the same group that tetanus stimulation of the LA in the mouse brain slices elicits modest LTP (1.2-to 1.4-fold increase to pre-tetanus) in the BLA (DeBock et al, 2003;Rammes et al, 2000). In our present study, however, we did not observe consistent BLA-LTP in wild-type mice.…”
Section: Ltp In the La-bla Synapsescontrasting
confidence: 90%
“…To test for G i /G o -dependent actions of AgRP, slices were preincubated for at least 4 h in either pertussis toxin (PTX) (5 ug/ml) or 8,8Ј-[carbonylbis(imino-3,1-phenylene)]bis-(1,3,5-naphthalenetrisulfonic acid) (NF023) (10 uM) at 37°C as previously described Freissmuth et al, 1996;DeBock et al, 2003;Garic-Stankovic et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The G i/o -protein antagonists PTX and NF023 were used Freissmuth et al, 1996). Brain slices were preincubated in PTX or NF023 as described previously (DeBock et al, 2003;Garic-Stankovic et al, 2005) before using for whole-cell recording. AgRP (100 nM) failed to decrease the frequency of EPSCs significantly in either PTX-pretreated slices (84 Ϯ 6% of control; p Ͼ 0.05; ANOVA; n ϭ 6) or NF023-pretreated slices (94 Ϯ 12% of control; p Ͼ 0.05; ANOVA; n ϭ 7) (Fig.…”
Section: Agrp Inhibition In Vglut2 Neurons In Vmh Is G I/o -Protein Dmentioning
confidence: 99%